2014
DOI: 10.3389/fpsyt.2014.00152
|View full text |Cite
|
Sign up to set email alerts
|

Brief Interventions for Hazardous and Harmful Alcohol Consumption in Accident and Emergency Departments

Abstract: The prevalence of alcohol abuse among patients treated in accident and emergency departments (A&E) is considered as substantial. This paper is a narrative review of studies investigating the effectiveness of brief interventions (BI) for hazardous and harmful alcohol consumption in A&E. A&E departments in hospitals (and other health care infrastructures) are commonly the place where serious consequences of alcohol drinking are seen and need to be tackled, supporting the suggested theoretical usefulness of deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…This marked reduction in alcohol use among our mobile MI group is sustained at 6 months, suggesting that motivation to change behavior continues after the immediate post‐intervention phase. Our findings contribute to the existing evidence that brief interventions help to reduce alcohol use in high‐ and low‐income countries , including studies in Kenya at the intersection of alcohol abuse and HIV/AIDS , and in some cases result in alcohol cessation .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This marked reduction in alcohol use among our mobile MI group is sustained at 6 months, suggesting that motivation to change behavior continues after the immediate post‐intervention phase. Our findings contribute to the existing evidence that brief interventions help to reduce alcohol use in high‐ and low‐income countries , including studies in Kenya at the intersection of alcohol abuse and HIV/AIDS , and in some cases result in alcohol cessation .…”
Section: Discussionsupporting
confidence: 58%
“…Evidence‐based brief intervention models for AUDs have been tested in primary care settings in high‐income countries but less so in low‐ and middle‐income countries . Motivational interviewing (MI) is a type of brief intervention that uses open‐ended questions, affirmations, reflective listening and summarizing as key tools .…”
Section: Introductionmentioning
confidence: 99%
“…The two most common behavioral therapies used in SBIRT programs are brief versions of cognitive behavioral therapy and motivational interviewing, or some combination of the two. There is substantial research on the effectiveness of SBIRT in reducing risky alcohol consumption (Bertholet et al 2005; Cochran et al 2015; Kaner et al 2009; Landy et al 2015; Ouimet et al 2013; Patton et al 2014; Steinka-Fry et al 2015; Teeters et al 2015; Whitlock et al 2004; Wojnar and Jakubczyk 2014). …”
Section: Five Important But Not Highest Priority Strategiesmentioning
confidence: 99%
“…Although their use has been recommended (Cunningham et al, 2009), brief interventions (BIs) have had mixed results in reducing or eliminating alcohol consumption among adolescent and ED patients (Nilsen et al, 2007; Havard et al, 2008; Yuma-Guerrero et al, 2012; Cochran et al, 2014; Dent et al, 2008; Wojnar and Jakubczyk, 2014; , 2008; Sommers et al, 2013; Bernstein et al, 2010; Academic ED SBIRT Research Collaborative, 2010; Newton et al, 2013). Furthermore, researchers have identified either decreases (Longabaugh et al, 2001; Blow et al, 2006) or no impact (Mello et al, 2013; D’Onofrio et al, 2012) of BIs on ED adult patient reported negative consequences of alcohol consumption as compared to control conditions.…”
Section: Introductionmentioning
confidence: 99%